Cloning of the trp-1 gene from neurospora crassa by complementation of a trpC mutation in Escherichia coli. - Keesey, J K (1982)
Studies with a hybrid plasmid containing 4.0 kilobase pairs of Neurospora crassa DNA cloned into plasmid pBR322 indicated that the plasmid restored to prototrophy a trpC mutant of Escherichia coli which lacked phosphoribosyl anthranilate isomerase but not a trpC mutant which lacked indole glycerol phosphate synthetase, that the relevant transcription was initiated at a promoter within the N. crassa DNA, and that the phosphoribosyl anthranilate isomerase could be specified by a subcloned segment of the original DNA.